2010
DOI: 10.1002/macp.201000459
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Behavior of Polydiacetylene‐Based Micelles

Abstract: The effect of photopolymerization on the structure, stability and encapsulation properties of polydiacetylene micelles containing nitrilotriacetic acid head groups are investigated. Micellar nanostructures of 7–10 nm diameter are identified that are invariant after polymerization. In the micelles, the polymerized ene‐yne chains are much shorter than in planar lipid membranes. SANS confirmed the presence of a monodisperse population of small particles before and after polymerization. It is shown that the CMC de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
23
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 37 publications
4
23
0
Order By: Relevance
“…The particle size obtained by TEM is somewhat smaller than those obtained by DLS measurement, which may be ascribed to the shrinking of the irregular vesicles fragments during the drying process [37]. All above results indicated that the protonation of the PDA would lead to the destabilization of the bilayers in the vesicle shell and the destruction of the PDA vesicles matrix, thereby allowing the contents to be released rapidly, which was in accordance with that of Wagner's previous work [38].…”
Section: Ph-controlled Release Behavior For the Designed Pda/azoecd Csupporting
confidence: 90%
“…The particle size obtained by TEM is somewhat smaller than those obtained by DLS measurement, which may be ascribed to the shrinking of the irregular vesicles fragments during the drying process [37]. All above results indicated that the protonation of the PDA would lead to the destabilization of the bilayers in the vesicle shell and the destruction of the PDA vesicles matrix, thereby allowing the contents to be released rapidly, which was in accordance with that of Wagner's previous work [38].…”
Section: Ph-controlled Release Behavior For the Designed Pda/azoecd Csupporting
confidence: 90%
“…The photostabilities of these Rhodamine 6G‐loaded PNADA/PDA complex vesicles with and without α‐CD were tested firstly by transmission electron microscopy (TEM) and dynamic light scattering (DLS) (as shown in the Supporting Information); both of which showed that the structure and size of these complex vesicles do not have any obvious change after 1 hour irradiation by UV (365 nm) and visible light (435 nm). However, the aggregation level of these complex vesicles with α‐CD dramatically dropped because of the removal of the interaction between α‐CD and complex vesicles under 365 nm light irradiation, which is consistent with our previous work 16. The photo‐induced controlled Rhodamine 6G release responses of the PNADA/PDA vesicles in the presence of α‐CD was observed.…”
supporting
confidence: 91%
“…All the above results confirm that the observed rapid release of Rhodamine 6G of the PNADA/PDA vesicles with α‐CD are indeed related to specific association of α‐CD with azobenzene moiety, instead of the blue‐to‐red phase transition of PDA matrix themselves. Previous works have reported that α‐CD could form an inclusion complex with the trans ‐azobenzene forms, while it hardly interacted with the cis ‐azobenzene moiety because of the mismatch between the host and guest 16. So α‐CD could form an inclusion complex with the trans ‐azobenzene forms due to specific association of α‐CD with the trans ‐azobenzene moiety and induce rapid release of Rhodamine 6G.…”
mentioning
confidence: 96%
“…Small-angle neutron scattering (SANS) studies provided further details about size and shape of the micellar nanostructures. [6,7] SANS experiments were recorded at increasing concentrations (from 0.3-1 wt %) in pH 12 D 2 O. Similar scattering signals were obtained and plotted as a function of the angle and the radius of gyration ((25.3 AE 1) ) was deduced from the Guinier approximation.…”
Section: Introductionmentioning
confidence: 99%
“…While the CMC of the nonpolymerized micelles was found to be 15 mg L À1 (measured using pyrene as extrinsic fluorescent probe), its value decreased below 1 mg L À1 after the photopolymerization step. [6] This lowered CMC value is indicative of an increased physical stability, which should help the polymerized micelles to survive dilute conditions in biological fluids.…”
mentioning
confidence: 98%